Local media reporting and influence on political communication in the north of Kosovo and Metohia - Marjanović, Milica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The influence of the media on the formation of public opinion is undeniable, regardless of which sphere of social and public importance is in focus. The political theory sees public opinion as a phenomenon of political practice essential for political activities, which was emphasized by some of our theoreticians (e.g. T. Đorđević). What is new in this work is the analysis of social structures in the areas that were covered by war events and in which we have a permanent state of frozen conflict. The text presents the results of empirical research among students of the University of Pristina with a temporary seat in Kosovska Mitrovica. The aim was to determine the influence of local media in the Serbian language from the north of Kosovo and Metohija in creating public opinion, the degree of trust in media reporting, as well as the existence of cooperation between political activists and professional communicators. The research method was applied, along with interview and survey techniques. Journalists from media companies in the municipalities of Kosovska Mitrovica and Zvečan were interviewed, and a total of 200 students from each faculty of the University of Pristina were surveyed. The sample is random according to the "snowball sampling" technique. The initial hypothesis was that there is a low level of cooperation and trust in reporting between representatives of local political parties and the media. Keywords: media, political communication, north of Kosovo and Metohija, ideology, public opinion, national context.